ANALISIS PERBANDINGAN ROUTING OSPF SINGLE AREA DAN MULTI AREA MENGGUNAKAN CISCO PACKET TRACER - Rohit Jhon Lamtama Purba; Yeremia Setya Maharman Gurning; Josua Anugrah Deo Tampubolon; Dedy Kiswanto (Jurnal Teknologi Informasi dan Komputer, 2025)
Computer networks are a crucial element in supporting electronic and real-time data exchange within various organizations. One of the commonly used routing protocols is OSPF (Open Shortest Path First), known for its efficiency and fast convergence. OSPF can be configured in two main types: single area and multi area, each with its own characteristics and advantages. However, there is still limited information regarding the performance comparison between the two in the context of network implementation. This research aims to compare the performance of OSPF Single Area and Multi Area through simulation in Cisco Packet Tracer, to provide recommendations based on network scale. The method used involves building two topologies with 15 routers: Single Area (Area 0) and Multi Area (Areas 0, 1, 2), then analyzing convergence time, LSDB size, the number of LSA, latency, and routing table complexity. The results show that Single Area is more suitable for small networks (<10 routers), while Multi Area is superior for large networks (>10 routers). In conclusion, Single Area is recommended for simple networks, while Multi Area is more appropriate for large networks with careful area planning.